Characteristics And Performance Of Men's Volleyball Athletes - ASTUTI, MELI; Hermanzoni, Hermanzoni; Masrun, Masrun; Setiawan, Yogi (Universitas Negeri Padang, 2025)
The purpose of this study was to look at the characteristics and performance of male volleyball athletes produced by the Ujung Gading Club, West Pasaman Regency, such as the components of anaerobic endurance, agility, flexibility, arm muscle explosive power, leg muscle explosive power. This type of research is quantitative by using descriptive method. Instruments in this study consisted of Running-based Anaerobic Sprint Test (RAST), Agility T-Test, Bridge Up-Test, One Hand Medicine Ball Put and Vertical Jump Test. The sample in this study amounted to 18 people, the data analysis technique used was percentage. The results obtained between the components of the physical condition are: (1) The current anaerobic endurance is in the medium category with an average of 8.29, (2) the current agility is in the good category with an average of 13 seconds, (3) The flexibility that they have now is in the medium category with an average of 73 cm, (4) The explosive power of the arm muscles that they have now is in the medium category with an average of 5.27 meters, (5) The explosive power of their leg muscles now classified in the medium category with an average of 96 kg-m/second, (6) The current level of nutritional status belongs to the normal category with an average of 18.7, (7) the age level currently belongs to the category 15 - 17 years with an average of 16 years.